Interview of Colin Bull by Brian Shoemaker - Bull, Colin (Byrd Polar Research Center Archival Program, 2007)
Key Individuals Mentioned 1. Frank Debenham, physiographer on Scott’s Last Expedition and first Director of the Scott Polar Research Institute, p.1 2. Herbert Ponting, photographer on Scott’s Last Expedition, p.2 3. Wilson, zoologist and artist on Scott’s Last Expedition, p.2 4. Stan Paterson, surveyor in Greenland, p.2 5. Hal Lister p.2, 15 6. Fritz Loewe, p.3, 4, 28, 29 7. Georgi, p.3, 4 8. Sorge, p.3, 4 9. Raymond Priestley, vice-chancellor of Birmingham University, p.5, 6, 19 10. Lancelot Fleming, p.8 11. Commander C. J. W. Simpson, p.8, 13 12. Taffy (Jack) Oakley, p.10 13. Roy Homard, went on Bunny Fuchs’s Transantarctic Expedition, p.11 14. Gillian Bull (Dr. Bull’s wife), p.14, 26, 27, 54 15. Bunny Fuchs, p.11. 14 16. Barrie McKelvey, p.15, 16 17. Peter Webb, p.15, 16 18. Dick Barwick, p.16, 20 19. Bob Nichols, p.21, 22 20. Bob Dawson, p.22 21. Ron Balham, p. 22 22. Ralph Wheeler, p.23 23. Ted Thorne, p.23 24. Bob Clark, p.23 25. Dufek, p.24, 25. 26. Tyree, p.24, 25 27. Dawn Rodley, later became Dawn Beck, p. 23, 24, 25, 26 28. Dick Goldthwait, p.26, 27, 30, 49, 52, 54 29. David Elliot, p.30, 49, 50, 51 30. John Mercer, p.31, 49 31. Kaye Everett, p.31, 49, 54 32. Mainly Mort, p.31, 32, 38, 40, 51 33. Tom Jones, p.31 34. Lois Jones, p. 38, 39, 41 35. George Llano, p.31, 32 36. Lonnie Thompson, p.32, 37 37. Ian Whillans, p.33 38. Gerry Holdsworth, p.33, 34 39. Cedo Marangunic, Chilean who came from Santiago to work with Dr. Bull on the Sherman Glacier, p.33, 36 40. Wayne Hamilton, p.35, 36 41. Olav Orheim, Head of the Norwegian Polar Institute, p.36, 37, 42 42. Ann Davey, p.37, 38 43. Almut Iken, p.38 44. Kay Lindsey, p.39, 41 45. Eileen McSavenney, p.39, 41 46. Terry Tickhill, p.39 47. Paul Dalrymple, p.40, 41 48. Kelly Welsh, p.41 49. Jim Zumberge, p.43 50. Larry Gould, p.43, 52, 57 51. John Heap, p.49 The media can be accessed at the links below. Audio Part 1: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Dr_Colin_Bull_1.mp3 Audio Part 2: ...